Luis Buñuel - Malvido Cordeiro, Sofía (Buñueliana, 2023)
Reseña de: Angulo, J. y Fernández, J. (eds.), Luis Buñuel, Donostia/San Sebastián, E.P.E. Donostia Kultura, Filmoteca Vasca (Colección Nosferatu), 2020, 307 pp.